Pengaruh Mata Kuliah Budaya Jepang Terhadap Kemampuan Beradaptasi Mahasiswa Peserta Internship di Jepang - Amalia, Aan; Jaohari, Abdul Latif; Sundasewu, Rama Ulun (Vocational College of Diponegoro University, 2025)
This study uses a qualitative descriptive method. Data collection was carried out through a questionnaire compiled based on indicators from the research objectives. The questionnaire was distributed via Google Form to 18 respondents who were active students and were undergoing an internship program. To find out about the influence of Japanese culture courses (Nihonjijo and Bijinesu Nihongo) on the adaptability of internship students in Japan, the author asked 10 questions to students of the Japanese Language Study Program at Widyatama University who were undergoing an internship program in Japan. The selection of respondents was carried out purposively, with the criteria that they had taken the courses in question and were directly involved in the world of work through internships. The data obtained from the questionnaire were analyzed using content analysis techniques, namely by grouping answers based on relevant themes or categories. Of the 18 respondents who were undergoing an internship program, most respondents wanted to go to Japan after getting to know Japanese culture more deeply through Nihonjijou lectures. Likewise with Bijinesu Nihongo lectures, most students felt a significant influence on the process of adapting and adjusting to the work environment and culture of Japanese society while undergoing an internship program.